2011
DOI: 10.1186/1471-2296-12-136
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the burden of herpes zoster and post herpetic neuralgia within primary care in rural Crete, Greece

Abstract: BackgroundResearch has indicated that general practitioners (GPs) have good clinical judgment in regards to diagnosing and managing herpes zoster (HZ) within clinical practice in a country with limited resources for primary care and general practice. The objective of the current study was to assess the burden of HZ and post herpetic neuralgia (PHN) within rural general practices in Crete, Greece.MethodsThe current study took place within a rural setting in Crete, Greece during the period of November 2007 to No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Across studies, a range of instruments have been used to assess the impact of HZ and PHN on mood, including the Hospital Anxiety and Depression scale (HADS) [7,15], 10,47 Short Italian Questionnaire (SIQ) [75,76], the Short Anxiety Screening Test (SAST) [56] and bespoke questions [58,77]. Up to 29% of patients with HZ reported feelings of moderate anxiety or depression, rising to 43% in patients with PHN.…”
Section: Resultsmentioning
confidence: 99%
“…Across studies, a range of instruments have been used to assess the impact of HZ and PHN on mood, including the Hospital Anxiety and Depression scale (HADS) [7,15], 10,47 Short Italian Questionnaire (SIQ) [75,76], the Short Anxiety Screening Test (SAST) [56] and bespoke questions [58,77]. Up to 29% of patients with HZ reported feelings of moderate anxiety or depression, rising to 43% in patients with PHN.…”
Section: Resultsmentioning
confidence: 99%
“…2,8,27,28,[32][33][34][35][36][37][38][39] Gender differences in the incidence of herpes simplex add strong support to the hypothesis that females have a differing response to latent viral infection and that this may account for their increased risk compared with men. 16 Studies conducted in numerous settings, and with various designs, have indicated an association between age and increasing zoster incidence.…”
Section: Sociodemographic Factorsmentioning
confidence: 85%
“…The anatomy of the primary afferent receptor is complete; however, the state is kept as abnormally hyperactive, which plays an important role in causing pain and maintaining abnormal pain25; this can be described as an “irritant receptor.” In addition, PHN is described as a central nervous system (CNS) abnormality (CNS sensitization), and abnormal pain and generalized C fibrosis are present at the same time; the completed and low-threshold A² fiber enters into the superficial layer of the dorsal horn of the spinal cord, directly connected with the two-stage pain-transmitting neuron, causing the pain 26,27. Moreover, for PHN, in the areas with obvious sensory deficits but no abnormal pain, there is persistent pain, or loss of sensory pain, which can be described as “afferent nerve block.”28 Finally, some studies have also shown that PHN is related to mental factors, as stress and anxiety can also lead to PHN 29…”
Section: Discussionmentioning
confidence: 99%